Sleep Hygiene Intervention Improves Sleep Time and Duration in High School Students - de Castro Corrêa, Camila [UNESP]; Silva, Gabryella Nery Teles Nogueira; Viana, Giovanna Régis; Lira, Amanda Lima E; Macedo, Gabriela Duarte; Weber, Silke Anna Theresa [UNESP] (Thieme, 2024)
Objective: To evaluate the effects of a sleep hygiene education program for adolescents to address excessive daytime sleepiness, insomnia, and sleep-related behaviors. Materials and Methods: The participants were 98 high school students from the 11th and 12th grades. A day-long health promotion action was conducted at their school science fair to disseminate relevant information about sleep disorders. Social status and sleep perception and habits were evaluated through the following validated questionnaires: the Brazilian Economic Classification Criteria, a questionnaire on sleep habits for adolescents, the Pediatric Daytime Sleepiness Scale, the Insomnia Severity Index, and the Sleep Time-Related Information and Communication Technology questionnaire. The questionnaires were administered before the fair and 12 months after participation, and the results before and after the intervention were compared by means of the Student t -test and the Fisher exact test. For the correlations involving the results, the Pearson correlation was used with the level of significance of p < 0.05. Results: A qualitative reduction in poor bedtime habits was observed after the intervention, such as watching television and leaving a cell phone on with sound. A higher frequency of use of electronic devices can affect school performance and contribute to later bedtime on weekends (p < 0.001). Excessive daytime sleepiness was correlated with the excessive use of electronic devices (p = 0.017). Conclusion: Some habits changed after the awareness intervention. There was an impact of the use of electronic devices on academic performance, on the regularity of bedtimes, and on excessive daytime sleepiness. We emphasize the importance of health education programs with sustainable actions following actual changes in behavior.
Keywords: adolescent; health promotion; sleep; sleep hygiene; technology